2022
DOI: 10.3390/cancers14030471
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic Therapy of Recurrent Medulloblastomas in Children and Adolescents: Results of the P-HIT-REZ 2005 Study

Abstract: Recurrent medulloblastomas are associated with survival rates <10%. Adequate multimodal therapy is being discussed as having a major impact on survival. In this study, 93 patients with recurrent medulloblastoma treated in the German P-HIT-REZ 2005 Study were analyzed for survival (PFS, OS) dependent on patient, disease, and treatment characteristics. The median age at the first recurrence was 10.1 years (IQR: 6.9–16.1). Median PFS and OS, at first recurrence, were 7.9 months (CI: 5.7–10.0) and 18.5 months (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
20

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 39 publications
2
4
0
20
Order By: Relevance
“…All but 2 patients in our study had disease recurrence at distant central nervous system sites with or without disease in the original tumor bed, a pattern that is consistent with previous observations . Prior studies have shown that surgery in isolated medulloblastoma relapses was associated with improved survival, albeit with limited long-term success in patients who had previously received irradiation . To avoid denying patients with complete resection access to the study, MEMMAT allowed patients with recurrent medulloblastoma to undergo resection before enrollment, and maintaining NED after a gross total resection was considered a benefit of the treatment combination.…”
Section: Discussionsupporting
confidence: 87%
“…All but 2 patients in our study had disease recurrence at distant central nervous system sites with or without disease in the original tumor bed, a pattern that is consistent with previous observations . Prior studies have shown that surgery in isolated medulloblastoma relapses was associated with improved survival, albeit with limited long-term success in patients who had previously received irradiation . To avoid denying patients with complete resection access to the study, MEMMAT allowed patients with recurrent medulloblastoma to undergo resection before enrollment, and maintaining NED after a gross total resection was considered a benefit of the treatment combination.…”
Section: Discussionsupporting
confidence: 87%
“…As also observed by Bakst and Gaab in their publications and now also con rmed in multivariable analyses, surgery, whenever possible, also plays a role at relapse and should be performed [11,29]. The presence of symptoms at relapse correlated with a worse prognosis and therefore, implicitly, with a lower e cacy of re-RT, as observed by the Toronto group [13].…”
Section: Discussionsupporting
confidence: 51%
“…The use of reirradiation (re-RT) was mostly a palliative treatment until a few years ago. It has been implemented only in more recent times, due to the potential toxicity after rst line craniospinal irradiation (CSI) and doubtful e cacy especially after higher CSI doses and in the case of disseminated relapse [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, this approach has become a standard of care that is still used in some institutions. However, the role of high-dose chemotherapy in this setting has been eventually questioned by cooperative groups or in institutional reviews [77][78][79][80]. The recent evidence that medulloblastoma subgrouping influences survival both at the time of diagnosis and after recurrence suggests that most long-term survivors of early reports on high-dose chemotherapy were probably group 4 patients [81].…”
Section: Chemotherapy As a Salvage Treatmentmentioning
confidence: 99%